Hospital emergency department challenges during COVID-19: a scoping review - Fahimeh Barghi Shirazi; Mostafa Modareszade; Ameneh Marzban; Mohammad Taghi Bastami; Hadis Amiri; Shandiz Moslehi (Health Science Monitor)
Background & Aims: The COVID-19 outbreak poses unique challenges for the emergency department, which is a vital hub for providing quality healthcare during the pandemic. Therefore, this study aims to identify the challenges faced by hospital emergency departments during the COVID-19 pandemic. Materials & Methods: A systematic review was conducted on studies published between 2019 and 2022. The search strategy employed both electronic and manual methods. The main keywords used in this systematic review included hospital, emergency department, COVID-19, epidemic, and challenge. Electronic databases such as MEDLINE (PubMed), Scopus, Web of Science, ProQuest, Google Scholar, Iran Medex, Magiran, and Scientific Information Database (SID) were searched. Additionally, a three-step screening process was used to select studies using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist. Finally, the data were analyzed thematically. Results: Out of the 1,357 studies retrieved, 11 were included in this systematic review. After analyzing the findings, four main categories of challenges were identified: leadership-related challenges, patient management, physical and mental fatigue among staff, and resource shortages. Conclusion: Healthcare systems need to be well prepared to deliver effective health services during epidemics. The quality of medical services is compromised by these emerging challenges, and this study provides evidence to support the development of an efficient framework for enhancing hospital emergency department services and addressing the challenges encountered during the COVID-19 epidemic.